CUIDADOS DE ENFERMAGEM AO SUJEITO USUÁRIO DE FLUOXETINA: REVISÃO DA LITERATURA - HILDEBRANDT, LEILA M.; FRANCO, LUIS F.; PIOVESAN, SOLANGE M. S.; DARONCO, VIVIAN F. (Salão do Conhecimento, 2013)
Resumo